Rate constant calculation for thermal reactions : methods and applications - DaCosta, Herbert; Fan, Maohong (Hoboken, N.J. : Wiley, 2012)
'This book provides an overview of the latest computational approaches to estimate rate constants for thermal reactions. It addresses the theories behind various first-principle and approximation methods that have emerged in the last twenty years with validation examples, and presents in-depth applications of those theories to a wide range of basic and applied research areas. When doing modeling and simulation of chemical reactions (as in many other cases), one often has to compromise between higher-accuracy/higher-precision approaches (which are usually time-consuming) and approximate/lower-precision approaches (which often has the advantage of speed in providing results). This book covers both approaches. It is augmented by a wide-range of applications of the above methods to fuel combustion, unimolecular and bimolecular reactions, isomerization, polymerization, and to emission control of nitrogen oxides'--Provided by publisher.
1. Overview of thermochemistry and its application to reaction kinetics / Elke Goos and Alexander Burcat -- 2. Calculation of kinetic data using computational methods / Fernando P. Coss{u2A6F} -- 3. Quantum instanton evaluation of the kinetic isotope effects and of the temperature dependence of the rate constant / Ji$1'b&(Bi Van{u2A69}cek -- 4. Activation energies in computational chemistry : a case study / Michael Busch, Elisabet Ahlberg, and Itai Panas -- 5. No barrier theory : a new approach to calculating rate constants in solution / J. Peter Guthrie -- 6. Quantum chemical and rate constant calculations of thermal isomerizations, decompositions, and ring expansions of organic ring compounds, its significance of cohbusion kinetics / Faina Dubnikova and Assa Lifshitz -- 7. Challenges in the computation of rate constants for lignin model compounds / Ariana Beste and A. C. Buchanan, III -- 8. Quantum chemistry study on the pyrolysis mechanisms of coal-related model compounds / Wang Baojun, Riguang Zhang, and Ling Lixia -- 9. Ab initio kinetic modeling of free-radical polymerization / Michelle L. Coote -- 10. Intermolecular electron transfer reactivity for organic compounds studied using Marcus Cross-Rate Theory / Stephen F. Nelson, and Jack R. Pladziewicz.s
Includes bibliographical references and index.
Keywords: Thermochemistry -- Mathematics; Chemical kinetics -- Effect of temperature on -- Mathematics; Numerical calculations